ANALYSIS OF THE IMPACT OF SUPI BEACH SEASONAL TOURISM ON THE SOCIO-ECONOMICS OF LOCAL COMMUNITIES IN SUNGAI PINANG DISTRICT - Rahayu, Puji Hervina; Taufik, Mirna; Damayanti, Nina (Quantitative Economics Journal, 2024)
Supi Beach in Sungai Pinang District is a seasonal tourism destination that offers tropical natural beauty, making it an attractive tourism destination.  With the charm of its beaches and outdoor activities that visitors can enjoy, Supi Beach is the only beach on Earth. The aim of this research is to analyze the impact of seasonal Supi beach tourism on the socio-economics of local communities in Sungai Pinang sub-district. This research uses a qualitative method, the data collection technique uses purposive sampling where the data collection process is carried out by observation, interviews and documentation. Meanwhile, data analysis techniques use several stages, namely data reduction, data presentation and drawing conclusions. The research results show that seasonal tourism has a positive impact in the form of increased income and employment opportunities for local communities, but there are also negative impacts such as environmental damage due to excessive tourism activities, to minimize negative impacts and maximize economic benefits for the community, and the Sungai Pinang community is not disturbed by the existence of Supi Beach tourism, making Sungai Pinang Village better known to people and helping to improve the economy of the local community.